Main flavonoids in the root of Scutellaria baicalensis cultivated in Europe and their comparative antiradical properties - Bochoráková, Hana; Paulová, Hana; Slanina, Jirí; Musil, Pavel; Táborská, Eva (Phytotherapy research, 2003)
The content of the main flavonoids in the root of Scutellaria baicalensis Georgi cultivated in Central Europe was evaluated using the new simple RP-HPLC method with gradient of acetonitrile in mobile phase. The main components of the roots were baicalin (8.12% of dry root mass) and wogonin glucuronide (2.52%). The content of flavonoids was comparable with the content in plants cultivated in natural localities. Five main flavonoids were evaluated for their scavenging ability with DPPH radical-generating system and due to limited solubility only two flavonoids were investigated for their ability to scavenge hydroxyl radical by the aromatic hydroxylation method. The total extract was also tested in both the experimental arrangements. In experiments with DPPH, only baicalin and baicalein displayed a significant scavenging effect, while the production of OH radicals generated by UV photolysis of H(2)O(2) was considerable decreased in the presence of baicalin and wogonin glucuronide. After comparison with results obtained for the total extract, it was concluded, that the scavenging activity of the extract against DPPH is mainly derived from baicalin. On the other hand, baicalin, wogonin glucuronide and probably other flavonoids participate in scavenging OH radical.
Keywords: scavengery volných radikálů; flavanony; Europe; Phytotherapy; Biphenyl Compounds; Evropa; Hydroxyl Radical; hydroxylový radikál; Chromatography, High Pressure Liquid; Plant Roots; rostlinné extrakty; glukuronidy; Scutellaria baicalensis; vysokoúčinná kapalinová chromatografie; flavonoidy; bifenylové sloučeniny; kořeny rostlin; Flavonoids; fytoterapie; Flavanones; Picrates; Humans; Free Radical Scavengers; inhibiční koncentrace 50; Inhibitory Concentration 50; Glucuronides; pikráty; Plant Extracts; šišák bajkalský; lidé